Genetic diversity analysis of lactic acid bacteria isolated from regional yogurt samples - Hossain, KM; Mazumder, B; Rahman, SMM; Hamid, MA (Bangladesh Journal of Livestock Research, 2021)
Probiotics are live, non-pathogenic microorganisms which have enormous health benefits. Yogurt is a potential source of probiotic bacteria. Lactic acid bacteria are the most common and major group of probiotic bacteria that can be found easily in different dairy products. The aim of study was the genetic diversity analysis using random amplified polymorphic DNA (RAPD) marker from regional yogurt samples of Bangladesh. Ten probiotic isolates from yogurt samples of different sweet meat shops of Sylhet and Mymensingh Divisions of Bangladesh were used. Morphological and biochemical tests were performed to ensure the presumptive probiotic characteristics of isolated bacteria. All isolates were cultured in De Man, Rogosa, and Sharpe (MRS) medium to exhort the growth of lactic acid bacteria. Genomic DNA was extracted by Ampicillin Lysozyme Tandem method. Four random RAPD primers were used in this study for detecting genetic diversity of these isolated bacteria. Among them, OPA 18 showed the maximum number of reproducible bands. Nei’s genetic distance was performed for determining Pair-wise Genetic Distance. UPGMA and NJ dendrogram were performed based on molecular data showing that all the isolates could be divided into two major clusters. Data analysis revealed that isolates from the same location were closely related and showed less genetic variation whereas, isolates from geographically different regions exhibited more genetic diversity. Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 55-63